2020
DOI: 10.3892/ijmm.2020.4520
|View full text |Cite
|
Sign up to set email alerts
|

miR‑21/PTEN pathway mediates the cardioprotection of geniposide against oxidized low‑density�lipoprotein‑induced endothelial injury via suppressing oxidative stress and inflammatory response

Abstract: Oxidized low-density lipoprotein (ox-LdL)-induced vascular endothelial damage, oxidative stress and inflammation play a vital role in the pathophysiology of atherosclerosis. Geniposide is the primary active ingredient from Gardenia jasminoides Ellis associated with anti-oxidative properties and cardioprotective action. However, the therapeutic mechanism of geniposide in atherosclerosis remains unclear. Hence, the present study aimed to elucidate the underlying mechanisms of geniposide in oxidative stress and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…The TLR4/MyD88/NF-κB pathway is regulated by geniposide in several human diseases, such as diabetic cognitive impairment [34], acute liver injury [35], and HCC [7]. Moreover, miR-21 [36], miR-373 [37], miR-214 [38] and miR-224 [8] are under the regulation of geniposide. Recently, several studies have demonstrated the correlation between geniposide treatment and lncRNAs [9,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…The TLR4/MyD88/NF-κB pathway is regulated by geniposide in several human diseases, such as diabetic cognitive impairment [34], acute liver injury [35], and HCC [7]. Moreover, miR-21 [36], miR-373 [37], miR-214 [38] and miR-224 [8] are under the regulation of geniposide. Recently, several studies have demonstrated the correlation between geniposide treatment and lncRNAs [9,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Geniposide, a major iridoid compound extracted from the gardenia fruit, Gardenia jasminoides (Rubiaceae), is a traditional Chinese medicine with a broad spectrum of pharmacological activities, such as conferring protection against inflammatory injury and stress [ 222 ]. Recent studies have focused on the potential cardioprotective effects of geniposide, demonstrating that geniposide treatment reduces plaque size and alleviates atherosclerosis-associated inflammatory injury [ 223 ].…”
Section: The Regulation Of Cvd-related Mirnas By Natural Antioxidamentioning
confidence: 99%
“…Recent studies have focused on the potential cardioprotective effects of geniposide, demonstrating that geniposide treatment reduces plaque size and alleviates atherosclerosis-associated inflammatory injury [ 223 ]. Geniposide attenuates endothelial injury and ROS generation by decreasing antioxidant enzyme activities, including SOD and CAT, which are directly associated with the enhancement of miR-21 expression in animal models of atherosclerosis [ 222 ]. The protective effect of geniposide on injured cardiomyocytes is also related to the upregulation of miR-145 expression [ 187 ].…”
Section: The Regulation Of Cvd-related Mirnas By Natural Antioxidamentioning
confidence: 99%
“…Genipin, a natural product derived from traditional Chinese medicine (TCM) Gardenia jasminoides , has shown anti-angiogenic, anti-proliferative, anti-inflammatory, and anticancer activities ( Jo et al, 2019 ; Zhang C. et al, 2020 ; Zhou et al, 2020 ). Kim et al (2020) have found that genipin can increase the expression of p53 and DRAM, induce apoptosis and autophagy, and enhance the sensitivity of AGS and MKN45 gastric cancer cell lines to OXA.…”
Section: Modulatory Effects Of Autophagy Inhibitors and Activators Onmentioning
confidence: 99%